ADRENAL GLAND MORPHOMETRY IN COVID-19 (Conferencea, 2024)
For morphometric analysis, less than 10 sections of each of the previously prepared microsamples were taken and processed on the NanoZoomer scanning device. These microsamples scanned on the NanoZoomer were subjected to multiplex confocal measurements using the QuPath-0.5.0+ ImageJ program. A total of 5 morphological and functional areas were calculated for the analysis of the adrenal gland tissue structures: 1) glomerular (GA), 2) fasciculata (FA), 3) reticularis areas (RA), 4) interstitial tissue (IT), and 5) areas occupied by pathological changes (PCh).